An innovative robotic platform for magnetically-driven painless colonoscopy - Bianchi, Federico (Ann Transl Med, 2017)
Colorectal cancer (CRC) represents a significant medical threat with a dramatic impact on the healthcare system with around 1.3 million patients worldwide, causing more than 700 thousand deaths annually. A key-aspect to successful and cost-effective disease management is represented by the early detection of CRC at asymptomatic stage. For this reason, population screening is highly recommended for patients older than 50 years or at high risk for familiarity. Currently, the standard endoscopic techniques do not meet this need. In recent years, innovative endoscopic robotic techniques and active locomotion devices have been developed as alternatives to conventional colonoscopy. The magnetically-driven robotic platform, presented by the authors, is conceived to perform less invasive and more comfortable colonoscopy with the aim to promote screening campaigns for detection of early colorectal neoplasm.